Component development for a high fidelity transient simulation of a coal-fired power plant using Flownex SE - Le Grange, Willie (Department of Mechanical Engineering, 2019)
Large coal-fired power stations are designed to be run predominantly at full load and optimum conditions. The behaviour of plants, operating at low load and varying conditions, is getting more and more attention due to the introduction of variable renewable generation on the grid. Consequently, the need for a fully transient high-fidelity system based model has grown, as this will enable one to study the behaviour of plants under such non-ideal conditions. This report details the development of a feedwater heater, deaerator and turbine component for such a high-fidelity transient system model using the Flownex Simulation Environment, a onedimensional thermohydraulic network solver. The components have been modelled all with the aim of using minimal design input data. The feedwater heater component model includes transient effects and thermodynamic relations to represent aspects such as heater performance, level control and transient inertia. In determining the heat transfer characteristics, the model makes use of plant-performance data and correlates the amount of heat transfer by using the feedwater mass flow as the load indicating parameter. This approach eliminates the need for specific geometrical details to calculate the effective heat transfer area. The level control is modelled by using a level representation built from using heat exchanger design methods. The turbine component is modelled by using Fuls’ Semi-Ellipse law or the pressure drop modelling and Ray’s semi-empirical method for the efficiency modelling. The model also contains transient effects, which include thermal inertia due to the shaft and casing, and rotational inertia due to the shaft. The deaerator component is modelled by adapting the model presented by Banda, and modifying the model to work under various conditions. This involved using curve fit methods in Flownex to use input data to model the pressure drop over the main condensate valve. Each of the mentioned components was validated and verified with plant data and finally packaged into a compound component which is a component consisting of a subnetwork in Flownex. These compound components further contain design inputs which are easily accessible by the user. The component models were integrated into larger networks in which various scenarios can be run. A short transient scenario was run on the low-pressure feedwater train of a specific power station. The scenario involved a turbine trip where the bled steam valves for the heaters were closed suddenly. The speed of the valves closing was however unknown and after closing the valves in approximately 10 seconds, results agreed relatively well with plant data. This illustrated the short transient capabilities of the feedwater heater component model. The three component models (feedwater heater, turbine and deaerator) were finally integrated into a regenerative Rankine cycle and was set up using minimal design data. The boiler, condenser and condensate pump were set as boundary conditions in the network but all extraction points for the network were connected. Steady-state results were obtained for various load cases and the main temperature, flow and pressure results were compared. Results agree well with plant data, even at low load conditions